Rotten Fruit and Cow Rumen as Local Microorganisms for Producing High-Quality Compost - Indasah, Indasah; Fitriani, Nurina (International Journal of Integrated Engineering, 2021)
Compost is an organic fertilizer that is utilized for farming to reduce the use of inorganic fertilizer. Compost utilization can improve the characteristics of soil and soil microbiology. Experiments were conducted in the Environmental Health Laboratory at Surya Mitra Husada Academy of Health, Kediri, Regional Health Laboratory of Kediri City, and Biology Laboratory and Soil Laboratory at Brawijaya University in May 2017. This study aims to discover the effects of concentration and fermentation period of rotten fruit and cow rumen on the quality of local microorganisms and compost. This study used a factorial Randomized Block Design (RBD) and 2 levels of rotten fruit and cow rumen concentration, 150 grams and 250 grams. These were fermented for different periods, 10 days and 20 days. The observed parameters were biological characteristics (bacterial population) and chemical characteristics (pH, Carbon (C), Nitrogen (N), Phosphorous (P), and Potassium (K).and carbon/nitrogen (C/N)). The results show that the concentration levels and fermentation periods had significant and insignificant values. The largest bacterial populations of cellulolytic microbes were 6.65 x 106 (local microorganisms) and 5 x 106 (compost). The highest pH levels were 3.11 (local microorganisms) and 7 (compost). The highest temperature was 29.50C (local microorganisms and compost). The highest levels of Carbon (C), Nitrogen (N), Phosphorous (P), and Potassium (K) were 7.26, 0.146, 0.067, and 0.409 respectively in Local microorganisms, while in compost, the values were 8.47, 0.81, 0.36, and 0.81 respectively. The highest carbon/nitrogen (C/N) ratios were 86 local microorganisms and 11 (compost).